Conversion of 2D line drawings to 3D models - Tay, Wei Xian. (2012)
This project aims to investigate the capability, speed, quality and stability of the three geometrical reconstruction systems, implemented based on three different methods, the cubic corner method, the optimization-based method and the hybrid method, which is a combination of the first two methods. Both accurate and inaccurate 2D input line drawings of a range of objects were tested and discussed. The objects range from simple geometrical objects to engineering objects with more complicated geometry. They can be made up of either all cubic corners or all non-cubic corners or a mixture of both. Inaccurate versions of a 2D drawing are created by modifying the shortest edge length connected to a vertex by a maximum percentage change (P) in a random direction. The P values selected in this report are 0.05, 0.1, 0.15, 0.2 and 0.25. In other words, the percentage change in the shortest edge length will be random, with the selected P values being the maximum.